2007
DOI: 10.1371/journal.pone.0000836
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Retinoic Acid Receptor Alpha Reveals the Growth Promoter Face of Retinoic Acid

Abstract: BackgroundRetinoic acid (RA), the bioactive derivative of Vitamin A, by epigenetically controlling transcription through the RA-receptors (RARs), exerts a potent antiproliferative effect on human cells. However, a number of studies show that RA can also promote cell survival and growth. In the course of one of our studies we observed that disruption of RA-receptor alpha, RARα, abrogates the RA-mediated growth-inhibitory effects and unmasks the growth-promoting face of RA (Ren et al., Mol. Cell. Biol., 2005, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 43 publications
2
30
0
1
Order By: Relevance
“…In ChIP experiments, we also observed enrichment of RAR- at the nSMase2 gene (data not shown), as was seen before (22). Collectively, these data agree with previous studies in MCF7 and T47D cells (9,22,23); moreover, the role that nSMase2 plays in ATRA-induced growth arrest (5) is consistent with the well-established antiproliferative role of RAR- (23,29,40,41). Additionally, as numerous studies have found that loss of RAR- signaling leads to alterations in mammary acini formation both in vivo and in vitro (27,(42)(43)(44), this suggests that the role of nSMase2 in ATRA-induced growth mRNA levels.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In ChIP experiments, we also observed enrichment of RAR- at the nSMase2 gene (data not shown), as was seen before (22). Collectively, these data agree with previous studies in MCF7 and T47D cells (9,22,23); moreover, the role that nSMase2 plays in ATRA-induced growth arrest (5) is consistent with the well-established antiproliferative role of RAR- (23,29,40,41). Additionally, as numerous studies have found that loss of RAR- signaling leads to alterations in mammary acini formation both in vivo and in vitro (27,(42)(43)(44), this suggests that the role of nSMase2 in ATRA-induced growth mRNA levels.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, emerging evidence has begun to point to a more protracted regulation of at the transcriptional level. Increases in nSMase2 expression have been reported in response to bone morphogenetic protein-2 (BMP2) (17,18), daunorubicin (19), cigarette smoke (20), confluence (6), the hedgehog signaling mediator cyclopamine (21), and all-trans retinoic acid (ATRA) (5,22,23). Notably, in the latter two cases, increased expression of nSMase2 was required for ATRA-induced growth arrest (23) and cyclopamine-induced apoptosis, respectively (21).…”
Section: Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…+ B cells was due exclusively to RA, or if additional mechanisms are involved we co-cultured 2 × 10 5 iDC in the presence of an equal number of syngeneic CD19 + B cells enriched from thawed, viable PBMC in the presence or absence of 1 mM of ER-50891, a pan-RAR selective antagonist [48] for 72 h. In Fig. 4d we demonstrate that the frequency of CD19…”
Section: Idc Fail To Promote Increased Cd19mentioning
confidence: 80%
“…Moreover, ATRA increased de novo Cer synthesis in human neuroblastoma cell lines (14). More recently, prolonged ATRA stimulation (72 h) of estrogen receptor-positive T47D cells increased nSMase2 expression and Cer and decreased expression of sphingosine kinase 1, responses that were suggested to be important for a reduction in cell proliferation (15). However, despite these studies, the wider effects of ATRA on the whole sphingolipid network are unknown.…”
mentioning
confidence: 99%